2018
DOI: 10.1186/s12864-018-4610-4
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific comparative genomics of isolates of the Norway spruce pathogen (Heterobasidion parviporum) and identification of its potential virulence factors

Abstract: BackgroundHeterobasidion parviporum is an economically most important fungal forest pathogen in northern Europe, causing root and butt rot disease of Norway spruce (Picea abies (L.) Karst.). The mechanisms underlying the pathogenesis and virulence of this species remain elusive. No reference genome to facilitate functional analysis is available for this species.ResultsTo better understand the virulence factor at both phenotypic and genomic level, we characterized 15 H. parviporum isolates originating from diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 89 publications
1
24
0
Order By: Relevance
“…Microorganisms 2019, 7, x FOR PEER REVIEW 6 of 14 demethylated while C sites are methylated at different loci [74]. Variation in the methylome of H. parviporum is observed during its asexual development and different lifestyles, reinforcing the dynamic nature of DNA methylation [72]. In M. oryzae, methylation peaks in the regions flanking coding sequences in mycelia and disappears in conidia and appressoria [44], suggesting that DNA methylation patterns change according to developmental stage.…”
Section: Dna Methylation and Rip Mutationmentioning
confidence: 96%
See 2 more Smart Citations
“…Microorganisms 2019, 7, x FOR PEER REVIEW 6 of 14 demethylated while C sites are methylated at different loci [74]. Variation in the methylome of H. parviporum is observed during its asexual development and different lifestyles, reinforcing the dynamic nature of DNA methylation [72]. In M. oryzae, methylation peaks in the regions flanking coding sequences in mycelia and disappears in conidia and appressoria [44], suggesting that DNA methylation patterns change according to developmental stage.…”
Section: Dna Methylation and Rip Mutationmentioning
confidence: 96%
“…In the following sections, we further discuss the distribution of DNA methylation in different genomic regions. An increasing number of studies have reported the presence of cytosine methylation in the gene bodies of many eukaryotic organisms, including fungi [72]. The gene body is considered to begin after the first exon because methylation of the first exon, like promoter methylation, leads to gene silencing [73].…”
Section: Patterns Of Dna Methylation In Fungal Plant Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently published reference genome of H. parviporum 96026 [14] enables a wider range of studies conducted in this species. Therefore, in our study, by employing whole-genome bisulfite sequencing, we uncovered the genome-wide DNA methylation pattern associated with different lifestyles (saprotrophy and necrotrophy) and asexual lifecycle stages (free-living mycelia and conidiospores) of H. parviporum 96026.…”
Section: Introductionmentioning
confidence: 99%
“…The LOD was also determined with 10-fold serial dilutions starting from 0.5 ng µL À1 genomic DNA extracts from strains 1987-1661/4 (H. parviporum), FOM0132 (H. irregulare), LSVM975 (H. abietinum) and 1960/ 56/4 (H. annosum s.s.). The genome size of H. annosum s.s. and H. irregulare was estimated to be approximately 31 and 33 Mb, respectively (Choi et al, 2017) and 33 Mb on average for H. parviporum (Zeng et al, 2018), whereas the genome size of H. abietinum remains to be determined. Because 1 pg of DNA corresponds to 965 Mb (Bennett & Smith, 1976), it is therefore possible to estimate the quantity of DNA in one nucleus of H. annosum s.s. (0.0321 pg), H. irregulare (0.0341 pg) and H. parviporum (0.0341 pg).…”
Section: Assessment Of Performance Criteriamentioning
confidence: 96%